Study on Simulation Method of Filtration for Oily Wastewater Treatment in Oilfield. Issue 1 (June 2021) - Wang, Y; Cao, B H; Gao, S; Ren, Y L; Zhang, R J; Peng, Z G
Abstract: Aiming at the filtration system in oily wastewater treatment, based on the simulation accuracy of wastewater treatment, the filtration process in wastewater treatment is numerically simulated, the corresponding mathematical model is established, and a hybrid modeling method combining trajectory tracking and network model method is proposed. Based on the analysis and calculation of the mechanical properties of suspended particles in the filter media, considering the coupling relationship between particles and channels, the dynamic displacement and the changes of channel diameter caused by the filtration process, the determination of channel diameter under different arrangement of filter media, the stress types of suspended particles in the channel, the establishment of mechanical model and the distribution of particles in the channel are studied in detail. Through the distance between the particle centre and the channel, it can be judged whether a particle can be adsorbed. From microcosmic to macroscopical, through the concentration calculated by mathematical model of particles and oil, the change rule and filtration effect of suspended particles and oil in the filtration process are obtained. This paper can increase the researchers' understanding of the trajectory tracking method, improve the accuracy of the proportion of filter materials in the research process of oily wastewater treatment technology, so as to obtain reliable filtration parameters of the target suspended solids.